Talking about terrorism: A study of vernacular discourse. (August 2016) - Jackson, Richard; Hall, Gareth
This article examines a neglected dimension of the dominant discourse of terrorism, namely, the vernacular, 'everyday narratives' of lay members of the public. While there are many studies of elite- and public-level discourses of terrorism, large numbers of public opinion and attitude studies, and a growing number of focus group studies on vernacular understandings of security and citizenship, there are few studies which specifically focus on lay discourses of terrorism. Importantly, there are even fewer studies which employ discursive psychology and conversation analysis as their primary methodological approach. Consequently, we do not know much about how ordinary people speak about in daily conversation – and therefore, how they understand or 'know' – what terrorism is, how it manifests, what its causes are, and how it is best dealt with. This article reports on some of the key findings of an empirical study of vernacular discourse about terrorism carried out in Aberystwyth, Wales. It reflects on what these findings tell us about how important political discourses are expressed in different arenas by different actors, how they are consumed and circulate, how they are resisted, how hegemonic they are in practice, and how they reflect cultural dispositions and the politics of legitimacy.